Odpowiedzi

Najlepsza Odpowiedź!
2010-01-07T21:48:27+01:00
A) 0,2(x+2)-0,3(y-2)=0,1
0,7(x-1)+0,1(y+5)=0,1

0,2x + 0,4 - 0,3y +0,6 = 0,1
0,7x -0,7 + 0,1y + 0,5 = 0,1

0,2x - 0,3y = 0,1 -1
0,7x + 0,1y = 0,1+ 0,2

0,2x - 0,3y = -0,9 /*10
0,7x + 0,1y = 0,3 /*10

2x - 3y = -9
7x + y = 3

7x + y = 3
2x - 3y = -9

y = 3 - 7x
2x -3(3-7x) = -9

y = 3 -7x
2x - 9 + 21x = -9

y = 3 - 7x
23x = -9 +9

y = 3 -7x
x = 0

y = 3 - 7*0
x= 0

y = 3
x = 0


b) ½(x-4)-2(y-3)=11
3(x-1)-⅓(y+6)=2

1/2x -2 -2y + 6 = 11
3x -3 - 1/3y -2 = 2

1/2x - 2y = 11 -4
3x -1/3y = 2+ 5

1/2x -2y = 7 /*2
3x -1/3y = 7 /*3

x - 4y = 14
9x -y = 21

x = 14 +4y
9*(14 + 4y) -y = 21

x = 14 +4y
126 + 36y -y = 21

x = 14 +4y
35y = 21 -126

x = 14 + 4y
35y = -105

x = 14 + 4y
y = (-105):35 = -3

x = 14 + 4*(-3)= 14 -12 = 2
y = -3

x = 2
y = -3